A collaborative multi-stakeholder analysis of the sheep and goats sector challenges in Europe - Belanche A.; Martín-García A.I.; Rose I.; Martín-Collado D.; Yáñez Ruiz D.R. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
This study aimed to identify the challenges of the sheep and goat sector in Europe as part of the iSAGE project. A total of 90 stakeholders were surveyed in 2018 following a participatory approach and each challenge was analysed in terms of i) relevance; ii) easiness to address and iii) stakeholders needed to take action. Differences in the relevance and easiness to address the challenges were compared between products (dairy vs meat), species (sheep vs goats), production system (intensive vs semi-intensive vs extensive), geographical region (Southern vs Central-Europe) and type of stakeholder (private vs public sector). A priority for action index was calculated to identify the key challenges, which combined high relevance and easiness to address. The high heterogeneity in the small ruminant sector across Europe was reflected in the variability observed in the perception of the challenges that this sector is facing. The main differences were found between regions (Southern vs Central Europe). The type of product and farming system explained moderate differences between challenges whereas species explained little differences. Overall, the top 10 challenges for prioritization included 5 internal weaknesses (Low promotion of local breeds; Poor business management training; Low professionalization; Slow adoption of innovations; Low adaptability of high producing breeds) and 5 external threats (Low consumer education; Low consumer knowledge on farming; Researchers not addressing real problems; Unfair trade/lack of traceability; Poor recognition of farming public services). Internal weaknesses need more action from the sector itself (farmers and associations), while external threats require action from governments in collaboration with the sector.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)